The physiology and control of re-greening in spathes of Zantedeschia : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Plant Physiology at Massey University, Palmerston North, New Zealand - Chen, Jianyu (Massey University, 2011)
Spathe re-greening is a primary determinant limiting postharvest quality of Zantedeschia Spreng. as a cut flower, pot- or landscape-plant. A treatment that can be utilised by growers to delay re-greening offers potential to improve the postharvest quality and provide a marketing advantage. To achieve this, and develop an understanding of the physiological mechanism of re-greening, this project investigated the changes in colour, levels and types of pigment, and differentiation of plastids in spathe tissue durng re-greening; and how this process was controlled by various factors including fructification, light and various plant hormones (e.g. cytokinin and gibberellin). In the hybrid ‘Best Gold’, spathe re-greening was initiated within three days after horticultural harvest-maturity and, within two weeks the whole abaxial surface of the spathe had re-greened. During this period, the adaxial surface did not re-green and remained yellow in colour. The change in colour of the abaxial surface primarily resulted from the accumulation of chlorophyll within the subepidermal layers, as reflected by a strong correlation between the colour coordinate hue angle (Hº) and total chlorophyll content in that surface (r = 0.98). Monitoring Hº can therefore, be used to evaluate the degree of re-greening for ‘Best Gold’ without chlorophyll analysis. The content of carotenoid (in particular lutein which was predominant) was comparatively steady during re-greening. From an ultrastructural perspective, spathe re-greening was characterized by redifferentiation of chloroplasts from chromoplasts, as compared with de novo synthesis of chloroplasts from proplastids. The redifferentiation of chloroplasts involved thylakoid reformation through multiple mechanisms. In addition to de novo synthesis of thylakoid by invaginations of the inner-envelope membrane, it is likely that the thylakoids were either derived from primary thylakoids or plastoglobuli present in mature chromoplasts. The occurrence of re-greening in the spathe of both Zantedeschia aethiopica and ‘Best Gold’ following the removal of the spadix prior to pollination, contradicted the hypothesis that re-greening was induced by fructification (Pais and Neves, 1982- 1983). Further to this, the occurrence of re-greening in the spathe of ‘Best Gold’ with a spadix naturally devoid of female flowers, and the re-greening of pigmented leaves devoid of any true flower parts, also contradicted this hypothesis. The current findings therefore, indicate that fructification is not necessarily a prerequisite for induction of re-greening. In absence of light, no chlorophyll accumulated in spathe tissue of ‘Best Gold’, but the initial redifferentiation of chloroplasts from chromoplasts, as characterized by the formation of double-membrane lamella, was noted. Without light however, redifferentiation of chloroplasts was not completed. These suggest spathe re-greening requires light for the process to complete, but the onset of re-greening can be induced in darkness. The application of 6-benzylaminopurine (BAP) stimulated re-greening in spathe tissue by enhancing accumulation of carotenoid and chlorophyll, and also stacking of grana. But the response to BAP was dependent on the presence/absence of light, the stage of re-greening, and which surface, i.e. abaxial or adaxial. In contrast, the application of gibberellin (GA3) retarded formation of double-membrane lamella, and thus delayed the onset of re-greening. Hence, a synergistic effect of BAP and GA3 in delaying the onset of re-greening was likely to be a result of co-regulation between BAP-stimulated accumulation of carotenoid and GA3-stimulated retardation of chloroplast redifferentiation. By integrating both light and hormonal factors, several methods were tested on the actual horticultural commodity, i.e. flowers (peduncle, spathe and spadix) of ‘Best Gold’, so as to evaluate their efficacy in delaying re-greening. Pulsing flowers in darkness at 5 ºC for 24-h in a solution containing both GA3 and BAP, was the most effective treatment in postponing re-greening, resulting in a seven-day delay in regreening of the spathe.
Content removed due to copyright restrictions: Chen, J., Funnell, K.A., & Woolley, D.J.(2009). Abaxial and adaxial surfaces of spathe tissue of Zantedeschia differ in their pattern of re-greening. Acta Horticulturae. 183, 217-224.
Keywords: Calla lilies; Zantedeschia; Postharvest physiology; Spathes; Re-greening